Stress in the Pathogenesis of Stroke (Eurasian Medical Research Periodical, 2023)
In our report, we analyze the data of the study on the parameters of the intensity of free radical processes and indicators of the state of the enzymatic and non-enzymatic antioxidant defense system in patients with stroke in the aspect of verification of oxidative stress in the pathogenesis of this disease.